2017
DOI: 10.15252/embj.201796476
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of viral and endogenous RNA by ZBP 1/ DAI induces necroptosis

Abstract: Nucleic acids are potent triggers for innate immunity. Double‐stranded DNA and RNA adopt different helical conformations, including the unusual Z‐conformation. Z‐DNA/RNA is recognised by Z‐binding domains (ZBDs), which are present in proteins implicated in antiviral immunity. These include ZBP1 (also known as DAI or DLM‐1), which induces necroptosis, an inflammatory form of cell death. Using reconstitution and knock‐in models, we report that mutation of key amino acids involved in Z‐DNA/RNA binding in ZBP1's Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(119 citation statements)
references
References 70 publications
(120 reference statements)
4
115
0
Order By: Relevance
“…We and other groups identified ZBP1 as a sensor of viral RNA (Maelfait et al, 2017;Sridharan et al, 2017;Thapa et al, 2016). Our current data bring forward the hypothesis that the detection of endogenous nucleic acids by ZBP1 contributes to inflammatory skin disease.…”
Section: Zbp1 Activation By Endogenous Nucleic Acids Induces Necroptosupporting
confidence: 70%
See 1 more Smart Citation
“…We and other groups identified ZBP1 as a sensor of viral RNA (Maelfait et al, 2017;Sridharan et al, 2017;Thapa et al, 2016). Our current data bring forward the hypothesis that the detection of endogenous nucleic acids by ZBP1 contributes to inflammatory skin disease.…”
Section: Zbp1 Activation By Endogenous Nucleic Acids Induces Necroptosupporting
confidence: 70%
“…ZBP1 contains two tandem N-terminal Z-form nucleic acid binding (Zα)-domains, which specifically interact with doublestranded (ds) nucleic acid helices in the Z-conformation, including Z-RNA and Z-DNA (Herbert, 2019). Others and our group have shown that engagement of ZBP1 upon virus infection crucially depended on nucleic acid sensing by intact Zα-domains (Maelfait et al, 2017;Sridharan et al, 2017;Thapa et al, 2016). The identity of viral ZBP1 agonists remains uncertain, and viral ribonucleoprotein complexes, RNA genomes, or viral transcripts have been suggested to interact with the Zα-domains of ZBP1 (Guo et al, 2018;Kesavardhana et al, 2017;Maelfait et al, 2017;Sridharan et al, 2017;Thapa et al, 2016;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, DAI has recently been shown to recognize viral RNA in addition to its role in DNA sensing to induce necroptosis (Maelfait et al, 2017; Thapa et al, 2016). The ability of STING to potentiate signals from many of these DNA sensors and bind CDNs places it central to the DNA sensing pathway for viral and bacterial infections.…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%
“…A series of gene knockout studies in mice have shown that caspase‐8 and receptor‐interacting protein kinase 1 (RIPK1) inhibit the activation of necroptosis mediated by Z‐DNA binding protein 1 (ZBP1), which is emerging as an important regulator of cell death and inflammatory responses . ZBP1 contains a domain that binds viral and endogenous DNA and RNA molecules that adopt a Z‐form (left‐handed double helix with zigzag pattern) . The involvement of ZBP1 in these experimental skin disease models points to important roles of endogenous nucleic acid species as initiators of skin inflammation.…”
Section: Epidermal Keratinocytes Suppress Inflammation During Normal mentioning
confidence: 99%
“…[74][75][76] ZBP1 contains a domain that binds viral and endogenous DNA and RNA molecules that adopt a Z-form (left-handed double helix with zigzag pattern). [76,77] The involvement of ZBP1 in these experimental skin disease models points to important roles of endogenous nucleic acid species as initiators of skin inflammation. The breakdown of the nucleus during cornification is a candidate starting point of nucleic acid-triggered pro-inflammatory processes.…”
Section: Epidermal Ker Atino C Y Te S Suppre Ss Infl Ammation Durinmentioning
confidence: 99%